Salivary antigen SP32 is the immunodominant target of the antibody response to Phlebotomus papatasi bites in humans. - Soumaya Marzouki; Maha Abdeladhim; Chaouki Ben Abdessalem; Fabiano Oliveira; Beya Ferjani; Dana Gilmore; Hechmi Louzir; Jesus G Valenzuela; Mélika Ben Ahmed (PLoS Neglected Tropical Diseases, 2012)
Background Zoonotic cutaneous leishmaniasis (ZCL) due to Leishmania major is highly prevalent in Tunisia and is transmitted by a hematophagous vector Phlebotomus papatasi (P. papatasi). While probing for a blood meal, the sand fly injects saliva into the host's skin, which contains a variety of compounds that are highly immunogenic. We recently showed that the presence of anti-saliva antibodies was associated with an enhanced risk for leishmaniasis and identified the immunodominant salivary protein of Phlebotomus papatasi as a protein of approximately 30 kDa. Methodology/principal findings We cloned and expressed in mammalian cells two salivary proteins PpSP30 and PpSP32 with predicted molecular weights close to 30 kDa from the Tunisian strain of P. papatasi. The two recombinant salivary proteins were purified by two-step HPLC (High-Performance Liquid Chromatography) and tested if these proteins correspond to the immunodominant antigen of 30 kDa previously shown to be recognized by human sera from endemic areas for ZCL and exposed naturally to P. papatasi bites. While recombinant PpSP30 (rPpSP30) was poorly recognized by human sera from endemic areas for ZCL, rPpSP32 was strongly recognized by the tested sera. The binding of human IgG antibodies to native PpSP32 was inhibited by the addition of rPpSP32. Consistently, experiments in mice showed that PpSP32 induced the highest levels of antibodies compared to other P. papatasi salivary molecules while PpSP30 did not induce any detectable levels of antibodies. Conclusions Our findings demonstrate that PpSP32 is the immunodominant target of the antibody response to P. papatasi saliva. They also indicate that the recombinant form of PpSP32 is similar to the native one and represents a good candidate for large scale testing of human exposure to P. papatasi bites and perhaps for assessing the risk of contracting the disease.